PRACTICAL IMPLICATIONS OF SPONTANEOUS ADVERSE DRUG REACTION REPORTING SYSTEM IN HOSPITALS-AN OVERVIEW - ABIDEEN P, SAINUL (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Adverse drug reactions (ADRs) are global problems of major concern which leads to morbidity and mortality. It causes 30 of hospitalized patients and lead 2-6 of all medical admissions. Spontaneous reporting of ADRs is the cornerstone of pharmacovigilance and is essential for maintaining patient safety. The necessity of a spontaneous ADR surveillance system is addressed by many authorities like World Health Organization, Food and Drug Administration, Joint Commission International and Uppsala monitoring center. However, existing postmarketing surveillance systems massively rely on spontaneous reports of ADRs which suffer from serious underreporting, latency, and inconsistent reporting. Studies estimated that only 6–10 of all ADRs are reported in hospitals. It is a very low percentage to go in deep and analyze the reason for the same and to resolve that underlying factors. Researchers proved that knowledge, attitude and false perceptions about the ADRs are the major challenges in the spontaneous reporting of ADRs. Which includes personal, professional, system related and organization related conflicts. Majority of them can improve by doing the system and personal targeted implications. Identifying, analyzing and working on these issues can improve the ADR surveillance system in hospitals to attain the patient safety. Understanding the pharmacovigilance, identifying and sorting out the obstacles of spontaneous reporting through an efficient pharmacovigilance department, continuous educational interventions, patient centered surveillance programs, health care team work efforts towards the detection of ADRs and implementation of the computer or personal assisted ADR trigger tool programs can furnish out a successful pharmacovigilance system in the hospitals and thereby we can constitute a good quality health care system. Key words: Spontaneous reporting system, adverse drug reaction, pharmacovigilance, Patient safety